Is ecological citizen something to be pedagogically made? an andragogical evaluation based on expert interviews - Morelli, Zeynep. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This study examines the concept of ecological citizenship from an interdisciplinary perspective and discuss the implications of the findings for adult environmental education. Through expert interviews (Bogner, Littig, & Menz, 2009) from the disciplines of education, ecology, economics, politics, and sociology (total N=5), the study identifies current debates on environmental issues, views on the parts the individual and systemic structures play on the path to ecological citizenship, and the implications of these for adult environmental education. This study designed as a qualitative research and expert interviews were analyzed using Qualitative Content Analysis (Mayring, 2000). Within the scope of ecological citizenship, the similarities and differences of the perspectives in the fields were analyzed and the dynamic relationships between the individual, society and the system were identified as guiding points for adult environmental education. The importance of the relationship between the individual and the system in the process and the need for the collective movement initiated by the individuals to lead the transformation of the system have emerged. According to the empirical analysis, adult education should be effective in providing ecological awareness, responsibility, and being a change agent competency to become an engaged citizen in ecological issues. The results support that adult education should offer capabilities that enable individuals to identify the underlying causes of ecological issues and to collaborate with others as pioneers of systemic change.
Keywords: Environmental education.; Environmentalism -- Social aspects.